Microfinance Risk Management at Bank Kalbar Syariah, Sambas Branch - Ahmad Yasir (Cross-Border Journal of Business Management, 2021)
This research was conducted to see whether the implementation of risk management at Bank Kalbar Syariah Sambas Branch is in accordance with the regulations with PBI No. 23/13 / PBI / 2011, because they still experience problematic financing for customers who are unable to fulfill their obligations to the bank in a timely manner. The approach and type in this research is a qualitative approach with descriptive character. This type of research is field research (field research). Researchers analyzed how the application of micro financing risk management, types of risks faced by microfinance and inhibiting and supporting factors in resolving micro-financing risks at Bank Kalbar Syariah, Sambas Branch in minimizing risk. The results showed that, the bank has implemented financing risk management in accordance with PBI No. 23/13 / PBI / 2011, the bank implements two risk management processes, namely before risk and after risk. Where the types of risk often faced by the Sambas Branch of the Kalbar Syariah bank are credit risk, market risk, and operational risk. In the settlement of micro-financing risks at Bank Kalbar Syariah, Sambas Branch is to cooperate with the insurer and insure collateral or guarantees from customers to the insurance company